Aproximación a la ética filosófica - D'Auria, Aníbal (2013)
The aim of this short paper is only to be a general and didactical introduction to Philosophical Ethics. Firstly, I will introduce some traditional issues of Meta-Ethics and Normative Ethics. Then, trough a panoramic tour of the history of Western philosophy, I will try to show some inflection points in moral thought from Antiquity to our present days. Finally, I will offer an essay on a personal position about the place of what is known as "applied ethics" within Philosophical Ethics.